10 Mbps slotted ring local area network - 8096 British Standards Institution (London : BSI, 1984)
Pt.1. Specification for the coding of bits and structure of slots and mini-packets -- Pt.2. Specification for configuration -- Pt.3. Specification for free-standing repeaters -- Pt.4. Specification for basic and enhanced class nodes with type 1 node / BTE interface -- Pt.5. Specification for monitor -- Pt.6. Specification for loggong station -- Pt.7. Specification for slave power supplies